EFEKTIVITAS EKSTRAK DAUN MAHKOTA DEWA (Phaleria macrocarpa) SEBAGAI ANTIBAKTERI UNTUK MENCEGAH SERANGAN BAKTERI Aeromonas hydrophila PADA IKAN GURAMI (Osphronemus gouramy) - Henny Christien; Yunasfi Djayus; Riri Ezraneti (AQUACOASTMARINE, 2014)
Disease prevention in fish using chemicals or antibiotics lead to microbial resistance. One of alternative to control the disease is to use plant extract. This study aimed to assess the antibacterial potential of mahkota dewa (Phaleria macrocarpa) leaf extract against disease causing bacteria Aeromonas hydrophila or Motil Aeromonas Septicemia (MAS) in fry of gouramy. The research method used was an experimental laboratory through ini vitro tests and 48-hour LC50 tests. The in vitro tests used 5 treatments and 2 replications, while the 48-hour LC50 for the test as many as five treatments and three replications. Treatment for in vitro test was a paper disc soaked in a solution of mahkota dewa leaf extract at a concentration of 250 ppm, 500 ppm, 600 ppm, 750 ppm, and the control (0 ppm), then placed on an agar medium that had been overgrown with Aeromonas hydrophila, and then incubated at 370C for 24 hours. Treatment of 48-hour LC50 test remedy, namely fry 4-6 cm sized gouramy marinated in mahkota dewa leaf extract solution at a concentration of 0%, 2%, 4%, 6%, and 8% for 48 hours. Data were analyzed descriptively. In vitro test results showed that mahkota dewa leaf extract at a concentration of 2% - 8% as an antibacterial potential of Aeromonas hydrophila with inhibition zone diameters ranging from 13,53 to 20,5 mm. The test results showed 48-hour LC50 of Gouramy fry mortality by 50% for gouramy fry is soaked in a solution of mahkota dewa leaf extract at a concentration of 600.536 ppm, based on EPA Probit analysis. The concentration of mahkota dewa leaf extract is safe for gouramy fry is 10% from the 48-hour LC50 value, that is 60.0536 ppm.Keywords : Aeromonas hydrophila, fry of Gouramy, mahkota dewa leaf